ORGANIZATIONAL STRUCTURE AND SPECIFIC ASPECTS OF STUDENTS' TECHNOLOGY "IMPROVEMENT OF THE METHODOLOGY OF INDEPENDENT WORK ACTIVITY IN THE INFORMATIONAL EDUCATIONAL ENVIRONMENT" - Qobilov T. A. (Web of Journals Publishing, 2023)
The importance of the problem in the teaching of mathematics is very great, and it is appropriate to use practical and non-standard problems in the educational process to increase students' interest in mathematics, to form the basis and competences related to science.
Keywords: Information, experience, skills, technology, method.